MCA Microsoft Certified Associate Azure Security Engineer Study Guide Exam AZ-500. - Brathwaite, Shimon (John Wiley & Sons, Incorporated, 2022)
Prepare for the MCA Azure Security Engineer certification exam faster and smarter with help from Sybex In the MCA Microsoft Certified Associate Azure Security Engineer Study Guide: Exam AZ-500, cybersecurity veteran Shimon Brathwaite walks you through every step you need to take to prepare for the MCA Azure Security Engineer certification exam and a career in Azure cybersecurity. You'll find coverage of every domain competency tested by the exam, including identity management and access, platform protection implementation, security operations management, and data and application security. You'll learn to maintain the security posture of an Azure environment, implement threat protection, and respond to security incident escalations. Readers will also find: Efficient and accurate coverage of every topic necessary to succeed on the MCA Azure Security Engineer exam Robust discussions of all the skills you need to hit the ground running at your first--or next--Azure cybersecurity job Complementary access to online study tools, including hundreds of bonus practice exam questions, electronic flashcards, and a searchable glossary The MCA Azure Security Engineer AZ-500 exam is a challenging barrier to certification. But you can prepare confidently and quickly with this latest expert resource from Sybex. It's ideal for anyone preparing for the AZ-500 exam or seeking to step into their next role as an Azure security engineer.